Campus development plan, 1945 - Unidentified mapmaker (Colorado State University. Libraries, 1945)
A map of the proposed changes to CSU's campus in 1945.
Not digitized by CSUL Digital Services.
Keywords: construction; planning; post war; landscaping; development; Colorado A & M College